Patients' knowledge and practice on disposal of medicines kept in households in South Africa: Findings and implications - Kesentseng Jackson Mahlaba; Elvera Anna Helberg; Brian Godman; Amanj Kurdi; Johanna Catharina Meyer (Wolters Kluwer Medknow Publications, 2022)
Objective: The disposal of unwanted, unused, or expired medicines is a concern. Currently, there is little knowledge regarding their disposal among patients in South Africa. Consequently, there is a need to address this. Methods: This was a descriptive and quantitative study with patients conducted among 16 primary health-care clinics (PHCs) in South Africa. A structured questionnaire was administered to 171 conveniently selected patients. Data on ideal disposal methods were collected and compared to actual disposal practices. Findings: 74.9% of patients reported having unused medicines at home, of whom 34.4% wanted these medicines disposed of. However, 64.9% did not know how to dispose of them, with 95.3% reporting having never been informed by health-care professionals of disposal methods. While patients prefer to return medicines to their PHC, only 7.0% did so. Patients' ideal disposal practices included designated collection task teams (25.1%) and dissolving their unused medicines in water (38.6%). However, current practices indicated that patients flushed medicines down the sewer (31.6%) or disposed of them in municipal bins (23.9%). Conclusion: Patients disposed of their unwanted medicines using incorrect disposal techniques, which they thought were correct. This urgently needs to be addressed.